2013
DOI: 10.1097/qai.0b013e318282d27f
|View full text |Cite
|
Sign up to set email alerts
|

High PMTCT Program Uptake and Coverage of Mothers, Their Partners, and Babies in Northern Uganda

Abstract: Our results show how a comprehensive PMTCT program emphasizing social and community engagement alongside medical care and support can succeed in a remote setting with multiple challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Among our representative sample of Salvadorian women of the lowest wealth quintile, less than 83% reported being screened for HIV during their last pregnancy. This rate is lower than the previously reported 97% for the year 2007 [12,19] and rates reported in other more or less developed countries, such as Canada and Uganda [20,23]. However, it is higher than the 76% of pregnant women served by the Indian Health Services who were screened for HIV in the United States in 2009 [24].…”
Section: Discussionmentioning
confidence: 64%
“…Among our representative sample of Salvadorian women of the lowest wealth quintile, less than 83% reported being screened for HIV during their last pregnancy. This rate is lower than the previously reported 97% for the year 2007 [12,19] and rates reported in other more or less developed countries, such as Canada and Uganda [20,23]. However, it is higher than the 76% of pregnant women served by the Indian Health Services who were screened for HIV in the United States in 2009 [24].…”
Section: Discussionmentioning
confidence: 64%
“…Three papers reported results of retrospective record reviews to evaluate programs to prevent mother to child transmission of HIV (PMTCT), two in northern Uganda and one in a refugee camp in Tanzania. One program found that higher proportions of HIV-positive pregnant women identified in ANC used anti-retroviral prophylaxis in northern Uganda compared with the national average [ 23 ]. The other two programs reported high numbers lost to follow-up before completing infant HIV testing at 18 months.…”
Section: Resultsmentioning
confidence: 99%
“…The adult prevalence of HIV in Uganda is 7.3% overall; 8.3% for women compared to 6.1% among men [2]. Access to antiretroviral therapy (ART) and prevention of mother to child transmission (PMTCT) programs enable women living with HIV (WLWH) to have children with minimal risks to their health and perinatal transmission [3]. However, being HIV positive and pregnant remains a challenging experience for women [4, 5]…”
Section: Introductionmentioning
confidence: 99%